2021
DOI: 10.1111/hae.14403
|View full text |Cite
|
Sign up to set email alerts
|

Women and girls with haemophilia receiving care at specialized haemophilia treatment centres in the United States

Abstract: Introduction: Females may have haemophilia with the same factor VIII (FVIII) or factor IX (FIX) levels as affected males. Characterization of females with haemophilia would be useful for health care planning to meet their unique needs. Federally-funded haemophilia treatment centres (HTCs) in the United States contribute data on all individuals with bleeding disorders receiving care to the Population Profile (HTC PP) component of the Community Counts Public Health Surveillance of Bleeding Disorders project. Aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 22 publications
(53 reference statements)
0
18
0
Order By: Relevance
“…The mean age was 41.6 years (21, 74), and the mean age of their affected child(ren) was 13.3 years (6 months, 25) (Table 1). Compared to other studies with a similar target population, our group has a comparable demographic breakdown 1–4,7,19 . Our population has a more significant African American population, a significant educated population, and includes biological and non‐biological mothers.…”
Section: Resultsmentioning
confidence: 90%
“…The mean age was 41.6 years (21, 74), and the mean age of their affected child(ren) was 13.3 years (6 months, 25) (Table 1). Compared to other studies with a similar target population, our group has a comparable demographic breakdown 1–4,7,19 . Our population has a more significant African American population, a significant educated population, and includes biological and non‐biological mothers.…”
Section: Resultsmentioning
confidence: 90%
“…This bias has often led to suboptimal clinical care and precluded women and girls with haemophilia (WGH) from clinical trial participation. Community Counts, the US surveillance database for bleeding disorders, reported that 0.5% of severe, 1.4% of moderate, and ∼20% of mild PwHA were female 60 …”
Section: Challenges In Patient Managementmentioning
confidence: 99%
“…Community Counts, the US surveillance database for bleeding disorders, reported that 0.5% of severe, 1.4% of moderate, and ∼20% of mild PwHA were female. 60 Recently, a new haemophilia female nomenclature was established by the International Society on Thrombosis and Haemostasis, considering FVIII and FIX plasma levels and bleeding phenotype. Consistent with males with haemophilia, females with low FVIII or FIX plasma levels of <0.01, 0.01-0.05, and >0.05-< 0.4 IU/ml were defined as having severe, moderate, and mild haemophilia, respectively.…”
Section: Women and Girls With Haemophiliamentioning
confidence: 99%
“…Although females with severe or moderate HB are quite rare, women and girls made up 24% of individuals with mild HB seen for care at US HTCs. 44 The genetic causes of hemophilia in those women and girls among whom a causative variant has been identified have recently been reviewed. 12 They include homozygosity (two copies of the same hemophilia-causing variant), compound heterozygosity (two different hemophilia-causing variants in trans), hemizygosity (a single hemophilia-causing variant with no normal allele), and heterozygosity (one hemophilia-causing variant and one normal allele).…”
Section: Females With Hemophilia Bmentioning
confidence: 99%